Islamic work ethics as mediator between trust and knowledge sharing relationship - Muhammad Mursaleen; Lutfullah Saqib; Kellie W. Roberts; Muhammad Asif (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
This research is intended to make few important contributions in the field of Ethics and Knowledge Management, firstly by investigating the contribution of Interpersonal Trust in Knowledge Sharing and secondly that how Islamic Work Ethics is important in making environment more conducive to Knowledge Sharing. The conclusion of this study is based upon the interpretation of results generated from survey data collected from the banking sector of Pakistan. All variables were measured on likert scale. The research represents that Islamic Work Ethics highly and positively mediates the relationship between Trust and Knowledge Sharing. Higher the level of Trust and Islamic Work Ethics, higher will be the level of Knowledge Sharing. The findings indicate that for knowledge sharing, ethical values and trust is necessary. The organization who wants to enhance knowledge sharing should create an ethical and trustworthy environment. According to the researchers knowledge it is the first study which measured the impact of trust on knowledge sharing in the banking sector and also the first to investigate the contribution of Islamic Work Ethics on Trust development and how it contributes in Knowledge Sharing. This research further explores that how trust mediates the relationship between Islamic Work Ethics and Knowledge Sharing.
Keywords: 330; Islamic work ethics; trust; knowledge sharing; mediation; ethical values